A comparative analysis of Inspector responses to complaints about psychosocial and physical hazards. Issue 1 (15th November 2021) - Popple, Sam; Way, Kïrsten; Johnstone, Richard; Croucher, Richard; Miller, Peta
Abstract: Work Health and Safety Inspectors are at the forefront of efforts to protect workers from harm from psychosocial hazards, yet the application of regulatory theory to their practice has been limited. Drawing on models of responsive regulation and strategic enforcement, we analyze extensive ( N = 46, 348) complaint and incident notification data from an Australian Work Health and Safety Inspectorate, to compare Inspectors' responses to psychosocial versus non‐psychosocial hazards. We found psychosocial hazards were less likely to be actioned than non‐psychosocial hazards. When they were actioned, psychosocial hazards saw more Inspector activity, but fewer enforcement notices than non‐psychosocial hazards. These findings are inconsistent with the version of responsive regulation espoused by the regulator. Our theoretical conclusion is that Weil's strategic enforcement approach is likely to offer greater possibilities for guiding future resource allocation.